Potential associations between perihepatic lymph node enlargement and liver fibrosis, hepatocellular injury or hepatocarcinogenesis in chronic hepatitis B virus infection. Issue 4 (16th June 2014) - Sato, Masaya; Hikita, Hiromi; Hagiwara, Shu; Sato, Mamiko; Soroida, Yoko; Suzuki, Atsushi; Gotoh, Hiroaki; Iwai, Tomomi; Kojima, Soichi; Matsuura, Tomokazu; Yotsuyanagi, Hiroshi; Koike, Kazuhiko; et al.
<x xml:space="preserve">Abstract</x> Aim Although perihepatic lymph node enlargement (PLNE) is frequently observed in chronic liver disease, little is known about PLNE in chronic hepatitis B virus (HBV) infection. We aimed to evaluate this issue. Methods We originally enrolled a consecutive 502 patients with chronic HBV infection. Among them, 288 patients without history of interferon‐based or nucleoside analog treatment and hepatocellular carcinoma (HCC) were primarily analyzed. Results PLNE was detected in 27 of 288 (9.4%) patients, which was fewer than that in chronic hepatitis C patients but more than that in subjects undertaking a general health examination as previously reported. The presence of PLNE was significantly associated with a higher probability of having an aspartate aminotransferase (AST) platelet ratio index of more than 1.5 (11.1% vs 1.5%, P = 0.01), a higher AST level (38.0 vs 26.8 U/L, P = 0.001), a higher alanine aminotransferase level (50.1 vs 28.0 U/L, P < 0.0001), and a lower platelet count (18.6 vs 20.6 × 104/μL, P = 0.048) after adjustment for sex and age. However, in our original sample (n = 502), PLNE was observed in 1.4% of the patients with HCC and/or its history whereas 9.2% of the patients without HCC, and the proportion was significantly lower in patients with HCC and/or its history (P = 0.03). Conclusion PLNE was associated with liver fibrosis and hepatocellular injury, but was negatively associated with HCC in chronic HBV infection.